Public Information : Desire, Disaster, Document. - Garrels, Gary; Lewis, Jim; Phillips, Christopher; Solomon-Godeau, Abigail; Riley, Robert R.; Weber, John S. (San Francisco : San Francisco Museum of Modern Art, 1994)
Akerman, Chantal ; Baldessari, John ; Clark, Larry ; Coleman, James ; Douglas, Stan ; Frank, Robert ; Goldin, Nan ; Gonzalez-Torres, Felix ; Graham, Dan ; Noland, Cady ; Richter, Gerhard ; Rosler, Martha ; Ruscha, Edward ; Wall, Jeff ; Warhol, Andy
Public Information : Desire, Disaster, Document, San Francisco Museum of Modern Art, San Francisco, January 18 - April 30, 1995
boek